2020
DOI: 10.1136/bmjopen-2020-038330
|View full text |Cite
|
Sign up to set email alerts
|

Effective SLOPE: EffectS of Lifestyle interventions in Older PEople with obesity: a systematic review and network meta-analysis protocol

Abstract: IntroductionObesity is highly prevalent in older adults aged 65 years or older. Different lifestyle interventions (diet, exercise, self-management) are available but benefits and harms have not been fully quantified comparing all available health promotion interventions. Special consideration must be given to functional outcomes and possible adverse effects (loss of muscle and bone mass, hypoglycaemia) of weight loss interventions in this age group. The objective of this study is to synthesise the evidence reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…This evidence map has been developed in the frame of the Effective SLOPE project (EffectS of Lifestyle interventions in Older PEople with obesity: a systematic review and network meta‐analysis; PROSPERO: CRD42019147286) 16 . The reporting of this study complies with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) for Scoping Reviews (PRISMA‐ScR) and the extension to the PRISMA Statement for Reporting Literature Searches in Systematic Reviews (PRISMA‐S) (Tables S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence map has been developed in the frame of the Effective SLOPE project (EffectS of Lifestyle interventions in Older PEople with obesity: a systematic review and network meta‐analysis; PROSPERO: CRD42019147286) 16 . The reporting of this study complies with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) for Scoping Reviews (PRISMA‐ScR) and the extension to the PRISMA Statement for Reporting Literature Searches in Systematic Reviews (PRISMA‐S) (Tables S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
“…Reviews and guidelines on obesity treatment in older adults have been published suggesting that lifestyle interventions in older adults are effective in reducing body weight and favoring combined interventions including dietary and exercise components 9,11,13–15 . The optimal content and dose of interventions, are not well established, one reason being the lack of systematic reviews with meta‐analyses enabling to identify optimal treatment strategies 11,16 . Clinical decisions about treatment should be based on outcomes of high‐quality randomized controlled trials 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since older persons have higher degrees of multimorbidity, frailty, sarcopenia, and nutritional risk, findings from younger people cannot be extrapolated to older people. Furthermore, one must take into account the negative effects of weight-loss therapies, such as decreased bone mineral density and muscle mass (13). Therefore, functional decline, functional restrictions, and the likelihood of unfavourable events like falls and fractures may all be higher in the elderly.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…Furthermore, the influence of perceived and real impediments on implementing lifestyle changes varies among younger and older persons. Despite these problems, current obesity guidelines still do not adequately address the treatment of obesity in older persons (13). Findings of a community-based study showed that the sample's median weight loss was 5% compared to their initial body weight.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%